Urine Biochemistry in the Early Postoperative Period after Cardiac Surgery: Role in Acute Kidney Injury Monitoring - Alexandre Toledo Maciel; Daniel Vitório (Case Reports in Critical Care)
We have recently suggested that sequential urine electrolyte measurement in critically ill patients may be useful in monitoring kidney function. Cardiac surgery is one of the leading causes of acute kidney injury (AKI) in the intensive care unit (ICU). In this paper, we describe the sequential behavior of urine electrolytes in three patients in the early (first 60 hours) postoperative period after cardiac surgery according to AKI status: no AKI, transient AKI, and persistent AKI. We have found that the patient with no AKI had stable and high concentrations of sodium (NaU) and chloride (ClU) in sequential spot samples of urine. AKI development was characterized in the other two patients by decreases in NaU and ClU, which have started early after ICU admission. Transient AKI was marked by also transient and less severe decreases in NaU and ClU. Persistent AKI was marked by the less favorable clinical course with abrupt and prolonged declines in NaU and ClU values. These electrolytes in urine had a behavior like a “mirror image” in comparison with that of serum creatinine. We suggest that sequential urine electrolytes are useful in monitoring acute kidney injury development in the early postoperative period after cardiac surgery.